In Vitro Cytotoxicity Activity And In Vivo Oral Toxicity Of Euphorbia hirta - Kwan, Yuet Ping (2014)

(untitled)
Euphorbia hirta is an annual plant that has been widely used in traditional medicine to treat various diseases. In vitro cytotoxicity, genotoxicity properties and in vivo toxicological evaluation of E. hirta methanol extract were investigated in this study. Various pharmacognostical parameters evaluation was carried out as per World Health Organization (WHO) guidelines procedure for the standardization of E. hirta extract. Euphorbia hirta adalah sejenis tumbuhan yang digunakan dalam perubatan tradisional secara meluas untuk mengubati pelbagai jenis penyakit. Sitotoksik, genotoksik secara in vitro dan penilaian ketoksikan secara in vivo ekstrak metanol daripada E. hirta telah diselidik dalam kajian ini.